2012
DOI: 10.1210/jc.2012-2234
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Zona Glomerulosa Insufficiency Causing Hyperkalemia in Primary Aldosteronism after Adrenalectomy

Abstract: Persistent postoperative hypoaldosteronism with hyperkalemia occurs in 5% of adrenalectomized PA patients through prolonged ZG insufficiency, requiring long-term fludrocortisone treatment. Potassium levels after adrenalectomy must be monitored to avoid life-threatening hyperkalemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 40 publications
8
88
1
6
Order By: Relevance
“…Postoperative hyperkalemia due to functional mineralocorticoid insufficiency in the contralateral adrenal was nevertheless reported in 15-30% of cases despite preventive prescription of preoperative spironolactone [19,20]. It was generally moderate and transient.…”
Section: Specific Complications and Short-term Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative hyperkalemia due to functional mineralocorticoid insufficiency in the contralateral adrenal was nevertheless reported in 15-30% of cases despite preventive prescription of preoperative spironolactone [19,20]. It was generally moderate and transient.…”
Section: Specific Complications and Short-term Follow-upmentioning
confidence: 99%
“…Spironolactone and potassium supplementation should be interrupted at surgery to reduce this risk, and kalemia should be checked postoperatively, especially in case of chronic kidney failure [20]. Even so, however, up to 5% of patients may require prolonged postoperative fludrocortisone treatment [19].…”
Section: Specific Complications and Short-term Follow-upmentioning
confidence: 99%
“…Nonetheless, postoperative hyperkalemia is seen in up to 30% of patients. 24,25 It is usually mild and transient, but MRA treatment and potassium supplements should be discontinued at the time of surgery, to minimize the risk, and serum potassium concentrations should be monitored closely, particularly in patients with chronic kidney disease (CKD). 25 In addition to the restriction of potassium-rich food, fludrocortisone has been used in rare cases of persistent hyperkalemia due to postoperative hypoaldosteronism.…”
Section: Unilateral Adrenalectomymentioning
confidence: 99%
“…25 In addition to the restriction of potassium-rich food, fludrocortisone has been used in rare cases of persistent hyperkalemia due to postoperative hypoaldosteronism. 24 Hormonal studies should be carried out for patients with high BP after surgery, to distinguish between persistent PA and associated essential hypertension.…”
Section: Unilateral Adrenalectomymentioning
confidence: 99%
“…In the trial reported by Parthasarathy et al (24) serum potassium level was modestly higher on 75-225 mg spironolactone than on 100-300 mg eplerenone (3.94 vs 3.83 mmol/l, P!0.001). Preoperative treatment with MRAs does not seem to increase the incidence of hypoaldosteronism or hyperkalemia after surgery (29). After surgery, MRAs should be withdrawn in the first postoperative day to avoid hyperkalemia (7).…”
Section: Mras In the Perioperative Periodmentioning
confidence: 99%